Recent advances on CRISPR/Cas system-enabled portable detection devices for on-site agri-food safety assay. (November 2022) - Qiu, Manyan; Zhang, Jingwen; Pang, Lidong; Zhang, Yu; Zhao, Qianyu; Jiang, Yujun; Yang, Xinyan; Man, Chaoxin
Abstract: Background: Agri-food safety has been considered as one of the most important public concerns worldwide. From farm to table, food crops and foods are extremely vulnerable to the contamination by a variety of pollutants from their growth and processing. Moreover, the SARS-CoV-2 detected in the food supply chain during COVID-19 pandemic has posed a greater challenge for rapid and on-site detection of agri-food contaminants in complex and volatile environments. Therefore, the development of rapid, accurate, and on-site detection technologies and portable detection devices is of great importance to ensure the agri-food security. Scope and approach: This review comprehensively summarized the recent advances on the construction of CRISPR/Cas systems-based biosensing technologies and their portable detection devices, as well as their promising applications in the field of agri-food safety. First of all, the classification and working principles of CRISPR/Cas systems were introduced. Then, the latest advances on the CRISPR/Cas system-based on-site detection technologies and portable detection devices were also systematically summarized. Most importantly, the state-of-the-art applications of CRISPR/Cas systems-based on-site detection technologies and portable detection devices in the fields of agri-food safety were comprehensively summarized. Impressively, the future opportunities and challenges in this emerging and promising field were proposed. Key findings and conclusions: Emerging CRISPR/Cas system-based on-site detection technologies have showed a great potential in the detection of agri-food safety. Impressively, the integration of CRISPR/Cas systems-based biosensing technologies with portable detection devices (e.g., nanopore-based detection devices, lateral flow assay, smartphone-based detection devices, and microfluidic devices) is very promising for the on-site detection of agri-food contaminants. Additionally, CRISPR/Cas system-based biosensing technologies can be further integrated with much more innovative technologies for the development of novel detection platforms to realize the more reliable on-site detection of agri-food safety. Graphical abstract: Emerging CRISPR/Cas system-enabled portable devices for the on-site detection of agri-food safety. Image 1 Highlights: The classification and working principles of Cas effectors were introduced. The latest advances on CRISPR/Cas system-based portable devices were summarized. Applications of CRISPR/Cas system-based portable devices in agri-food safety were summarized. Remaining challenges and opportunities in this promising field were proposed.